2017
DOI: 10.1080/13691058.2017.1331468
|View full text |Cite
|
Sign up to set email alerts
|

Women’s decision-making about self-protection during sexual activity in the deep south of the USA: a grounded theory study

Abstract: Many women continue to become infected with HIV, particularly in the Southeastern USA, despite widespread knowledge about methods to prevent its sexual transmission. This grounded theory investigation examined the decision-making process women use to guide their use or non-use of self-protective measures when engaging in sexual activity. Participants included women in the Mississippi cohort of the Women’s Interagency HIV Study who were infected with or at high risk for HIV. Theoretical sampling was used to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Many nonrural areas offer a plethora of social services that help to address these issues. However, rural communities are often limited in the availability of resources for persons living with HIV . Interestingly, American Indian/Alaska Native women in rural and metropolitan areas had higher levels of viral suppression than those in MSAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many nonrural areas offer a plethora of social services that help to address these issues. However, rural communities are often limited in the availability of resources for persons living with HIV . Interestingly, American Indian/Alaska Native women in rural and metropolitan areas had higher levels of viral suppression than those in MSAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, rural communities are often limited in the availability of resources for persons living with HIV. 24,25 Interestingly, American Indian/Alaska Native women in rural and metropolitan areas had higher levels of viral suppression than those in MSAs. It is possible that availability of health care through Indian Health Services facilities, which are primarily located outside of MSAs, resulted in improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This idea of sexual silence at the community level has been described in other literature and in different populations. 29,30 Many participants reported that black MSM are more at risk of HIV because they are not exposed to information on sexual health in their homes or communities until they are well into adulthood. It was perceived that there was a larger acceptance among white communities to discuss sexuality and HIV prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…People think that guys who are on PrEP are overly promiscuous and all they want to do is have all this unprotected sex, these orgies and all this stuff. ''-CP120, 29 A few participants also expressed their concerns about PrEP use directly leading to increased promiscuity among users as a major barrier for their own use of PrEP. This led some to be concerned about initiating PrEP themselves, because they were concerned about not only stigma related to PrEP but also actual increase in promiscuity as a result of its use: A subtheme also emerged of a few participants feeling a lot of the stigma surrounding PrEP was due to its association with HIV.…”
Section: Stigma Related To Prepmentioning
confidence: 99%
“…Though, studies have revealed the in uence of socio-demographic, marital and psychological factors, gender norms, and women's position within the household as well as community factors on women's ability to negotiate sex in many parts of the globe has been examined [35,[51][52][53]. Other studies considered condom use and sexual negotiation among young men and women [54]; women's household decision-making autonomy and safer sex negotiation [55]; women's decision-making about self-protection during sexual activity [56]; household decisionmaking among married women [57] and women's reproductive health decision-making [58]. Despite the governmental and non-governmental efforts to minimize new infections in most countries with generalized or high burden epidemics, including Nigeria, the comparison and measurement of the interaction in uence of family structure and decision-making autonomy on attitudes towards negotiating safe sexual practices has been quite limited.…”
Section: Introductionmentioning
confidence: 99%